Fisher accessibility and habitat complexity influence the distribution of adult Cherax cainii (Decapoda: Parastacidae) in a water supply reservoir. Issue 11 (8th August 2019) - Beatty, Stephen J.; Ryan, Tom; Morgan, David L.
Abstract: Almost one third of all freshwater crayfishes are threatened with extinction. The factors influencing the distribution of freshwater crayfishes in lentic systems are poorly understood, hampering the conservation and enhancement of those populations. Cherax cainii is the third largest freshwater crayfish in the world and is endemic to south‐western Australia. The distribution of the species has declined markedly, largely attributable to secondary salinization and habitat decline. There is the potential for population enhancement through habitat restoration and the restocking of reservoirs that act as important non‐salinized refuges; however, there is limited understanding of the distribution and habitat associations of C. cainii in these systems. Mark–recapture was undertaken to determine the population abundance and fine‐scale distribution of C. cainii in a large reservoir over a 5‐month period, with generalized linear mixed modelling used to determine those factors that explained the variation in its distribution. Cherax cainii distribution in the reservoir was positively associated with complex habitat (large woody material) and the level of inaccessibility to humans, and negatively associated with depth. The population had a non‐uniform distribution within the reservoir with significant hot‐ and cold‐spots present and there was limited distance between recaptures during the coolest period of the year. The findings suggest that C. cainii would benefit from the provision of additional complex habitat in such habitat depauperate reservoirs to provide increased shelter from predators. It may also be vulnerable to localized depletion through legal and illegal fishing pressure. The study highlights the importance of understanding habitat preferences and movement patterns of freshwater crayfish to underpin their conservation.